(untitled) (Annals of Medical Research, 2026)
Aim: Traumatic brain injury (TBI) significantly contributes to mortality and disability in children aged 0-18 years. TBI is a potentially fatal health emergency, and when severe, children are at high risk of mortality and neurological morbidity. Our goal is to identify the various etiologies of head trauma in pediatric patients and provide examples of preventive measures to prevent further trauma. Our research also highlights the socioeconomic burden of patients with TBI. Materials and Methods: The institutional electronic health record (HBYS) was queried for all pediatric patients admitted to the Neurosurgery Clinic in Kayseri City Hospital, diagnosed with traumatic head injury by the neurosurgery service, and registered for discharge between January 2021 and June 2025. This study investigated 180 pediatric head trauma cases. Patient nationality (Republic of Turkey or Other) and length of hospital stay (HLOS) were also used as demographic data. Results: The mean age was 7.2±5.32 (min-max: 0-17) years. Of the 146 children, 146 were Turkish citizens. 15 of the children, 15 (8.3%) underwent cranial surgery, and 69 (38.3%) had a history of intensive care admission. The mean length of hospital stay was 2.73±3.03 (min-max: 1-18) days. The most common type of head trauma in children was linear fractures due to falls from heights and from the same level (p<0.05). Conclusion: Implementing primary prevention strategies, preventing secondary neurological injuries, and collaborating with organized emergency teams can facilitate early intervention in patients with head trauma. Thus, early diagnosis and treatment of high intracranial pressure can reduce the adverse effects of TBI. These preventive measures can reduce morbidity and mortality in children. This study comprehensively examines the etiology and demographic characteristics of pediatric head trauma in a single center in the Central Anatolia Region.